Global and quantitative proteomic analysis of dogs infected by avian-like H3N2 canine influenza virus - Su, Shuo; Tian, Jin; Hong, Malin; Zhou, Pei; Lu, Gang; Zhu, Huachen; Zhang, Guihong; Lai, Alexander; Li, Shoujun (Frontiers in Microbiology, 2015)
Canine influenza virus A (H3N2) is a newly emerged etiological agent for respiratory infections in dogs. The mechanism of interspecies transmission from avian to canine species and the development of diseases in this new host remain to be explored. To investigate this, we conducted a differential proteomics study in two-month old beagles inoculated intranasally with 106 TCID50 of A/canine/Guangdong/01/2006 (H3N2) virus. Lung sections excised at 12 hours post-inoculation (hpi), 4 days, and 7 days post-inoculation (dpi) were processed for global and quantitative analysis of differentially expressed proteins. A total of 17,796 proteins were identified at different time points. About 1.6% was differentially expressed between normal and infected samples. Of these, 23, 27 and 136 polypeptides were up-regulated, and 14, 18 and 123 polypeptides were down-regulated, at 12 hpi, 4 dpi, and 7 dpi, respectively. Vann diagram analysis indicated that 17 proteins were up-regulated and one was down-regulated at all three time points. Selected proteins were validated by real-time PCR and by Western blot. Our results show that apoptosis and cytoskeleton-associated proteins expression was suppressed, whereas interferon-induced proteins plus other innate immunity proteins were induced after the infection. Understanding of the interactions between virus and the host will provide insights into the basis of interspecies transmission, adaptation, and virus pathogenicity.